Employee Performance Model: Analysis of Training, Organizational Culture and Work Environment by Mediating Work Discipline - Alkaf, Abdur Rachman; Yunus, Eddy; Ady, Sri Utami (SEISENSE Journal of Management, 2024)
Purpose- This research provides a new strategy for stakeholders regarding factors influencing the improvement of employee performance through work discipline in the Indonesian Air Force.Design/Methodology- This is quantitative research. The research population consisted of all Indonesian Air Force employees. The sample size for this research was 400 employees. Data collection was survey with a questionnaire. This study utilized Smart PLS version 3.2.9 and data analysis employed PLS-SEM.Findings- The findings indicate that organizational culture, work environment and work discipline significantly impact employee performance. Additionally, training, organizational culture, and work environment have an effect on work discipline and work discipline acts as a mediator in the relationship between training, organizational culture and work environment with employee performance.Practical Implications- The practical implications can assist the Indonesian Air Force in enhancing employee performance and creating a better work environment. Through appropriate actions, the organization can achieve improved outcomes in pursuing its objectives.